2012
DOI: 10.1128/jb.01210-12
|View full text |Cite
|
Sign up to set email alerts
|

Conjugal Transfer of a Virulence Plasmid in the Opportunistic Intracellular Actinomycete Rhodococcus equi

Abstract: Rhodococcus equi is a facultative intracellular, Gram-positive, soilborne actinomycete which can cause severe pyogranulomatous pneumonia with abscessation in young horses (foals) and in immunocompromised people, such as persons with AIDS. All strains of R. equi isolated from foals and approximately a third isolated from humans contain a large, ϳ81-kb plasmid which is essential for the intramacrophage growth of the organism and for virulence in foals and murine in vivo model systems. We found that the entire vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 59 publications
(87 reference statements)
6
41
0
Order By: Relevance
“…The protection ensured by the EPS matrix during stress conditions, including exposition to UV radiation (Espeland et al 2001) and metal toxicity (Teitzel & Parsek 2003) may be highly advantageous during the saprophytic life of R. equi. In this way, Tripathi et al (2012) showed a mechanism by which the virulence plasmid can move among R. equi in the soil. These authors highlight a possible relationship between conjugation and biofilm formation by environmental R. equi.…”
Section: Discussionmentioning
confidence: 97%
“…The protection ensured by the EPS matrix during stress conditions, including exposition to UV radiation (Espeland et al 2001) and metal toxicity (Teitzel & Parsek 2003) may be highly advantageous during the saprophytic life of R. equi. In this way, Tripathi et al (2012) showed a mechanism by which the virulence plasmid can move among R. equi in the soil. These authors highlight a possible relationship between conjugation and biofilm formation by environmental R. equi.…”
Section: Discussionmentioning
confidence: 97%
“…Relaxases play a key role in the conjugation of circular plasmids, nicking the supercoiled double-stranded DNA (dsDNA) and leading the nascent DNA strand into the recipient cell in conjunction with a type IV secretion system (T4SS), which forms the transport channel (50,51). Indeed, deletion of traA has been shown to prevent the transfer of the equine pVAPA circular virulence plasmid (39). Interestingly, however, the pVAPN traA relaxase gene is corrupted (5=-terminal deletion affecting the first 75 codons, including the gene start and part of the TrwC relaxase domain, and frameshifts in the 3=-terminal region) and probably nonfunctional.…”
Section: Resultsmentioning
confidence: 99%
“…Transfer of the virulence plasmid between R. equi bacteria was investigated by using a mating protocol essentially as previously described (39). Cultures of donor and recipient R. equi strains grown overnight in BHI were harvested by centrifugation, resuspended in phosphate-buffered saline (PBS) to a cell density of Ϸ10 7 CFU, mixed Ϸ1:1, and spotted in a 5-l drop onto BHI agar.…”
Section: Methodsmentioning
confidence: 99%
“…However, despite the superficial similarities in virulence strategy, the underlying mechanisms are different. The subversion of the normal functioning of macrophages by R. equi is dependent on the presence of a conjugative plasmid harboring a pathogenicity island encoding a family of six virulence-associated proteins (Vap) that do not occur in M. tuberculosis (10)(11)(12). One of these, the cell envelope-associated protein VapA, is required, but not sufficient, for the inhibition of phagosomal maturation and for intracellular growth (13)(14)(15)(16).…”
mentioning
confidence: 99%